Three year school based intervention for Tobacco prevention in the region of Sousse: quasi experimental design 2009-2014 - Ferdaous Ouni; Sana Bhiri; Jihen Maatoug; Rim Ghammam; Jihen Sahli; Hassen Ghannem (Tobacco Induced Diseases, 2018)
Background Tobacco use is one of the biggest public health threats the world has ever faced. Tunisia is one of the countries suffering from the heavy burden of tobacco use. It is in this context that the Chronic Disease Prevention Research Center in Sousse established a school based intervention for tobacco control and prevention. Our objective was to evaluate the feasibility and effectiveness of our intervention in tobacco control and prevention by the evaluation of smoking behavior among schoolchildren at pre and post assessment in both intervention and control groups.